Pengelolaan Sumber Daya Hutan dan Dampak Sosial Kawasan HTI di Kecamatan Bukit Batu Kabupaten Bengkalis Provinsi Riau - Heriyanto; Edi Sably; Asrol; fathurahman; Elinur Elinur; Budi Mulianto; Azmansyah; Detri Karya (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
HTI development involves many parties and stakeholders, one of which is the community living around the industrial forest area, whose existence cannot be separated from the forest. The location of the service in Bengkalis Regency is focused on Bukit Batu District. Data and information were collected through interviews and Focused Group Discussions. The results of the identification of social impacts found negative impacts from the existence of HTI companies on the people in the survey villages, namely land ownership conflicts, labour recruitment, and road dust that interfered with the residents' health. While the positive impact felt by the community is CSR assistance such as commemorating the anniversary of Indonesia's independence, sports competitions, and others. Additionally, the forest management efforts that must be carried out are socialization of a persuasive approach to the community to resolve conflicts between HTI companies and community lands, provide the widest possible opportunity for local workers in companies according to their level of education and experience, and prevent road dust so that it no longer disturbs the health of the population.